Updated checklist of Hemerobiidae (Neuroptera) from Brazil and new distributional records in the Neotropical Region - Rosa Lara, Rogeria Ines; Perioto, Nelson Wanderley [UNESP] (Inst Nacional Pesquisas Amazonia, 2016)
Hemerobiidae (Insecta, Neuroptera) is a cosmopolitan Glade that comprises about 600 described species distributed into 26 genera. Since the publication of revisions to Hemerobius, Megalomus, Nusalala and Nomerobius, new records have been added in literature and taxonomic modifications have occurred at the genus level. The aim of this study was to update a checklist of Hemerobiidae species from Brazil and of specimens deposited at Colecao de Invertebrados do Instituto Nacional de Pesquisa da Amazonia (INPA), Manaus, Brazil; in order to summarize the geographical data of species in Brazilian states and in the Neotropical Region and to present new distributional data. The INPA collection holds 19 nominal species (55.2% of the all specimens identified at species level) of hemerobiids into eight genera and six subfamilies, mainly from the Neotropical Region; the remaining studied specimens were identified to the genus level. Megalomus marginatus is reported for the first time in Brazil and Nusalala dispar in Ecuador. Moreover, ten new records for the Brazilian states are presented: two to Nusalala tessellata and Hemerobius, and one each to Megalomus impudicus, Notiobiella maculata, Sympherobius ariasi, Megalomus, Nusalala and Sympherobius.
Keywords: Hemerobius; INPA; Megalomus; Nomerobius; Nusalala